2018
DOI: 10.1101/392886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of narrowband amplitude and phase from electrophysiology signals for phase-amplitude coupling studies: a comparison of methods

Abstract: Many functional connectivity studies based on electrophysiological measurements, such as electro-and magnetoencephalography (EEG/MEG), start their investigations by extracting a narrowband representation of brain activity time series, and then computing their envelope amplitudes and instantaneous phases, which serve as inputs to subsequent data processing. The two most popular approaches for obtaining these narrowband amplitudes and phases are: bandpass filtering followed by Hilbert transform (we call this the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Among existing methods, [35] introduced a time lag to the amplitude, while [44] swap amplitude and phase trials and [57] swap time blocks, cut at a random point. The latter method, with only two blocks, has been described as the most conservative strategy to generate the distribution of PAC that can be observed by chance [47]. Finally, this null distribution is then used to perform non-parametric inference or to correct the measure estimated from the data (usually by subtracting the mean and divide by the deviation of this distribution).…”
Section: Statistical Analysis Of Pacmentioning
confidence: 99%
See 2 more Smart Citations
“…Among existing methods, [35] introduced a time lag to the amplitude, while [44] swap amplitude and phase trials and [57] swap time blocks, cut at a random point. The latter method, with only two blocks, has been described as the most conservative strategy to generate the distribution of PAC that can be observed by chance [47]. Finally, this null distribution is then used to perform non-parametric inference or to correct the measure estimated from the data (usually by subtracting the mean and divide by the deviation of this distribution).…”
Section: Statistical Analysis Of Pacmentioning
confidence: 99%
“…One issue that has been raised is that, since PAC is computed across time, non-stationary signals can cause the appearance of spurious coupling [47]. An illustrative example taken from the same study explains that if there is an induced phase locking of lower frequencies and simultaneously a high frequency power increase, a coupling between them is going to be observed.…”
Section: Event-related Phase-amplitude Coupling (Erpac)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is still no consensus on the minimal data length (i.e. the number of cycles) that is required or the most appropriate filtering methods [ 48 , 49 ]. It has also recently been shown that spurious PAC can occur for a variety of reasons that may be difficult to systematically control [ 48 , 50 52 ].…”
Section: Introductionmentioning
confidence: 99%